European Society for the Study of Coeliac Disease (ESsCD) guideline for coeliac disease and other gluten‐related disorders. Issue 5 (1st June 2019) - Al-Toma, Abdulbaqi; Volta, Umberto; Auricchio, Renata; Castillejo, Gemma; Sanders, David S; Cellier, Christophe; Mulder, Chris J; Lundin, Knut E A
Abstract : This guideline presents recommendations for the management of coeliac disease (CD) and other gluten‐related disorders both in adults and children. There has been a substantial increase in the prevalence of CD over the last 50 years and many patients remain undiagnosed. Diagnostic testing, including serology and biopsy, should be performed on a gluten‐containing diet. The diagnosis of CD is based on a combination of clinical, serological and histopathological data. In a group of children the diagnosis may be made without biopsy if strict criteria are available. The treatment for CD is primarily a gluten‐free diet (GFD), which requires significant patient education, motivation and follow‐up. Slow‐responsiveness occurs frequently, particularly in those diagnosed in adulthood. Persistent or recurring symptoms necessitate a review of the original diagnosis, exclude alternative diagnoses, confirm dietary adherence (dietary review and serology) and follow‐up biopsy. In addition, evaluation to exclude complications of CD, such as refractory CD or lymphoma, should be performed. The guideline also deals with other gluten‐related disorders, such as dermatitis herpetiformis, which is a cutaneous manifestation of CD characterized by granular IgA deposits in the dermal papillae. The skin lesions clear with gluten withdrawal. Also, less well‐defined conditions such as non‐coeliac gluten sensitivity (NCGS) and gluten‐sensitive neurological manifestations, such as ataxia, have been addressed. Newer therapeutic modalities for CD are being studied in clinical trials but are not yet approved for use in practice.